Minding the gaps: assessing and addressing clinical research core competencies across a network of Canadian cancer centres - Sundquist, Stephen; Kato, Diana; Chowdhury, Raisa; Samara, Christine; Dancey, Janet E. (Frontiers in Pharmacology, 2023)
The Canadian Cancer Clinical Trials Network (3CTN, the Network), established in 2014 to address the decline in academic cancer clinical trials' (ACCT) activity, has successfully achieved incremental year-over-year accrual targets as well as implemented recognized performance measures and supports for improving efficiency and quality of trial activities at member sites across Canada. As part of efforts to address ongoing challenges of staff recruitment, retention, and turnover in academic institutions that have been more recently exacerbated by the pandemic, the Network's Performance Strategy Sub-Committee (PSC) oversaw surveys of site clinical research professionals intended to capture workforce development status and identify knowledge gaps using the Joint Task Force Core Competency Framework (JTF CCF) as the standard basis for assessment. Accountable to the 3CTN Management Committee, the PSC consists of clinical research operations experts across Canada responsible for overseeing implementation and monitoring progress of this initiative. Staff at 3CTN's adult sites evaluated and reported trial personnel core competencies and gaps according to each domain/leveled competency statement of the framework. The most frequently noted competency gaps were in the domains of: Investigational Product Development and Regulation (28%); Scientific Concepts and Research Design (16%); and Study and Site Management (14%). Reported data was compiled and represented in the 3CTN Core Competency Report, developed as a web-based, interactive tool enabling members and stakeholders to filter data to enumerate and quantify workforce competency gaps at their site, within their node of affiliated sites, or across the national Network. Concurrently, an environmental scan and review of education resources was conducted and reviewed by the PSC. Embedded links to curated learning and development resources were incorporated into the report and associated with each domain/leveled competency statement to provide ready access to high-quality learning and development resources where needed. In the This is a provisional file, not the final typeset article remaining years of its current strategic plan, 3CTN will continue to monitor, develop collaborative initiatives to target prioritized clinical research competency gaps and create opportunities for ongoing assessment and reporting by sites to capture changes in workforce core competencies over time.